(3OSJhQ GdOhdI GdeOfjI GdMOjKI (B:s ((3QDjI JWHjbjI ddbGYOI GdOSJhQjI aj GdOhdI GdeOfjI GdMOjKI Hjf GdCUGdI hGdeYGUQI(B) /s - (3GdSjO, eUWai NejS,s 1985- ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2014)
(3gPG GdYed jYGUQ aJQI ef Cge aJQGJ LeghQjI eUQ GdYQHjI hgj KhQI (B25 (3jfGjQ (B2011 (3hcjajI ESbGW GdQFjS eHGQc hJYWjd OSJhQ (B1971 (3hEfTGA EYdGf OSJhQj aj (B19 (3eGQS (B2011 (3ef bHd GdeLdS GdYScQj hKe EUOGQ EYdGf eced Ke HYO Pdc EfTGA OSJhQ LOjO ddHdGO aj YgO GdQFjS GdeNdhY eQSi hddCSa de jdjb HOhdI eKd eUQ dgG ecGfJgG hMVGQJgG hJGQjNgG GdYQjb Ke YGUQ CjVG KhQI (B30 (3jhfjI (B2013 (3hESbGW OSJhQ GdCNhGf hEfTGA OSJhQ jHfi eUQ ef LOjO hJfGhd gPg GdCMOGK aj gPG GdcJGH hgj jMci JGQjN GdOSGJjQ GdYGdejI hWQb CfTCgG hWQb ESbGWgG(B.s
(3HHdjhLQGajI (B: (3UaMI (B323-329.s
Keywords: (3GdOhdIs; (3GdbGfhf GdOSJhQjs